Diálogos com docentes: construindo possibilidades para o ensino de ciências por investigação com a educação infantil - Magnago, Mirella Pereira Caliari (2021)
The purpose of the present study is to investigate the comprehension constructed from developing formative assessments, which were accomplished by faculty members who work with early childhood education at CEIM (Centro de Educação Infantil Municipal) in the city of Colatina, Espírito Santo, under the perspective of Inquiry-Based Science Education (IBSE). Based on Inquiry-Based Science teaching conjectures and Vygotsky cultural-historical perspective, this current study brings forth specific goals: to identify the understanding and attainability of apprehension provided by teachers, during activities and classes that present a possibility for the incorporation of IBSE in pedagogical practices with early childhood education; and to analyze the comprehension created from developing formative assessments. The research was qualitative, inspired by action research as critical-collaborative research (FRANCO, 2012, 2014, 2019). Being carried out during the current SARSCoV-2 pandemic, it utilized digital media, supported by Moran (2014), to provide interaction between participants and the data production. For the data analysis, content analyses were selected, established by Bardin (2002) and Franco (2005). The results indicate that the understanding and apprehension elicited by teachers during the activities are related: the relevance of teachers actively listening to children’s ideas and problems; the perception about IBSE with nursery education, evidence of inquiring activities implemented by teachers; and, at last, acknowledging the necessity for adequate qualification to work with early childhood education. The study indicates, as a conclusion, that the training carried out contributed to freshen and reopen the teachers’ mindset on their pedagogical practices and collaborative work; the need for continuing education which addresses an emancipatory pedagogical praxis. This research proposes the assembly of an educational guide for faculty members, to support other teachers and academic personnel to enliven and freshen their daily class activities and practices and to further enforce the implementation of Inquiry-Based education and teaching from early childhood.